Properties of Sorption Complex and Humic Acids in Sandy Soils Fertilized with Sewage Sludge - E. Stanczyk-Mazanek; L. Stepniak (Chemical Engineering Transactions, 2013)
One of the methods of disposal of sewage sludge, which is based on its fertilizing properties, is its use in nature, e.g. in farming (if all the permissible standards are met). However, the sludge used for soil fertilization might also contain heavy metals which cause soil contamination and are accumulated in plants. The effect of application of organic fertilizers on soil reaction and other properties of sorption complex are also essential. The authors of the present study aimed at analysis of the effect of use of sewage sludge and selected organic fertilizers on changes in sorption properties in the fertilized soils. For comparison purposes, sewage sludge was introduced to sandy soil. One organic addition was also composted pine bark. The experiment was carried out under conditions of pot experiment. The following doses of organic fertilizers were used: 0, 10, 50,100 and 200 Mg·ha-1, which was calculated per pot with 10 kg of sandy soil. After 12 months from fertilization, changes in active and hydrolytic acidity were analysed in the fertilized foundations. The contents of organic matter, total of alkali in sorption complex S, soil sorption capacity T and content of humic acids in fertilized soils was also determined.